Ethics in Economics : An Introduction to Moral Frameworks. - Wight, Jonathan B. (Redwood City : Stanford University Press, 2015)
Ethics in Economics provides an introduction to the ethical systems that underpin economic debates. Jonathan B. Wight considers how outcomes, duties, and virtue work together in economic life to create wealth by addressing moral hazards and building trust.
Intro -- Contents -- Figures -- Acknowledgments -- Preface -- Part I: Moral Frameworks -- Chapter 1: Why Ethics Matters -- Chapter 2: Outcomes -- Chapter 3: Duties, Rules, and Virtues -- Part II: Evaluating the Economy -- Chapter 4: Welfare and Efficiency -- Chapter 5: Pareto Efficiency and Cost-Benefit Analysis -- Chapter 6: Critiques of Welfare as Preference Satisfaction -- Part III: Topics in Ethics and Economics -- Chapter 7: Moral Limits to Markets -- Chapter 8: The Science behind Adam Smith's Ethics -- Chapter 9: Ethics and the Financial Crisis of 2008 -- Chapter 10: Economic Justice: Process versus Outcomes -- Chapter 11: Economic Justice: Equal Opportunity -- Chapter 12: Ethical Pluralism in Economics -- Notes -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Economics -- Moral and ethical aspects; Electronic books